The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7759/cureus.13380
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Musculoskeletal Care During the COVID-19 Pandemic: Evaluating Readiness of Saudi Citizens

Abstract: Introduction: Since coronavirus disease 2019 (COVID-19) was announced as a global pandemic, it has become important to control the pandemic with several approaches, including limiting hospital visits. Telemedicine is a good option to help reduce in-person visits during the pandemic. Saudi Arabia has prepared for this pandemic by implementing applications, such as Tetamman and Seha. In this study, we aimed to determine the readiness of the Saudi population to use telemedicine for musculoskeletal care during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This experience has been reported in Saudi Arabia through previous studies, which described the potential and acceptability of DHTPs among the Saudi population. The evidence showed positive results, considering the challenges and limited perspective of clinicians, patients, policymakers, and stakeholders [3,[20][21][22][23][24][25]. Previous national surveys in Saudi Arabia have demonstrated that the DHTPs for COVID-19 have the advantage of wide access, user-friendly interface, ease of use, and high acceptance rate [22][23][24][25][26][27].…”
Section: Determinants For Optimising Dhtpsmentioning
confidence: 99%
“…This experience has been reported in Saudi Arabia through previous studies, which described the potential and acceptability of DHTPs among the Saudi population. The evidence showed positive results, considering the challenges and limited perspective of clinicians, patients, policymakers, and stakeholders [3,[20][21][22][23][24][25]. Previous national surveys in Saudi Arabia have demonstrated that the DHTPs for COVID-19 have the advantage of wide access, user-friendly interface, ease of use, and high acceptance rate [22][23][24][25][26][27].…”
Section: Determinants For Optimising Dhtpsmentioning
confidence: 99%
“…This experience had been reported in Saudi Arabia through previous studies, which described the potential and acceptability of DHTPs among the Saudi population. The evidence showed positive results, considering the challenges and limited perspective of clinicians, patients, policymakers, and stakeholders [3,[19][20][21][22][23][24]. Previous national surveys in Saudi Arabia demonstrated that the DHTPs for COVID-19 had the advantage of wide access, user-friendly interface, ease of use, and high acceptance rate [21][22][23][24][25][26].…”
Section: Mobile Health Applicationsmentioning
confidence: 99%